Maternal exposure to carbon monoxide and fine particulate matter during pregnancy in an urban Tanzanian cohort. (15th March 2016) - Wylie, B. J.; Kishashu, Y.; Matechi, E.; Zhou, Z.; Coull, B.; Abioye, A. I.; Dionisio, K. L.; Mugusi, F.; Premji, Z.; Fawzi, W.; Hauser, R.; Ezzati, M.
Abstract: Low birthweight contributes to as many as 60% of all neonatal deaths; exposure during pregnancy to household air pollution has been implicated as a risk factor. Between 2011 and 2013, we measured personal exposures to carbon monoxide (CO) and fine particulate matter (PM2.5 ) in 239 pregnant women in Dar es Salaam, Tanzania. CO and PM2.5 exposures during pregnancy were moderately high (geometric means 2.0 ppm and 40.5  μ g/m 3 ); 87% of PM2.5 measurements exceeded WHO air quality guidelines. Median and high (75th centile) CO exposures were increased for those cooking with charcoal and kerosene versus kerosene alone in quantile regression. High PM2.5 exposures were increased with charcoal use. Outdoor cooking reduced median PM2.5 exposures. For PM2.5, we observed a 0.15 kg reduction in birthweight per interquartile increase in exposure (23.0  μ g/m 3 ) in multivariable linear regression; this finding was of borderline statistical significance (95% confidence interval 0.30, 0.00 kg; P  = 0.05). PM2.5 was not significantly associated with birth length or head circumference nor were CO exposures associated with newborn anthropometrics. Our findings contribute to the evidence that exposure to household air pollution, and specifically fine particulate matter, may adversely affect birthweight.